ANALISIS PE,ILIHAN SKEMA PENDANAAN INVESTASI BISNIS GAS METANA-B (GMB) PT PERTAMINA (PERSERO)Studi kasus: Pengelolaan Bisnis GMB di PT Pertamina Hulu Energi - , Endah Lestari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This paper aims to analyze the calculation on the economic Coal Bed Methane (CBM), using a model contract for the oil and gas Production Sharing Contract (PSC) from the three options of funding scenarios, namely: Option A, Pertamina in the carry-up to POD (Plan of Development )phase or end of third year